Capacities and technological trends in the non-industrial panela production process. A study of technological monitoring - Hernández - Cely, Sandra Rosario; Torres - Zamudio, Marleny (Universidad Francisco de Paula Santander, 2021)
The production of panela is of great importance in the economy and food security of the rural and urban sector in Colombia, starting from this fundamental economic axis, in this research work the application of a process of technological surveillance in the production of artisanal panela is presented. For the development of the research, a search was carried out for studies and technological developments in information sources such as databases of scientific journals and patents. Which in turn were adapted to the methodological guidelines established in the UNE 166006: 2018 standard. R + D + i management: surveillance and intelligence system. With the development of this work, it was possible to diagnose and establish the technological inventory, the use of measurement devices, control and organoleptic characteristics in the production of artisan panela. Obtaining as a final result, the protocol or methodology for implementing specific technological developments for a panela production system.